The implications of complexity, systems thinking and philosophy for pediatricians - Jochen Ehrich; Jürgen Manemann; Velibor Tasic; Natale Gaspare DeSanto (BMC, 2021)
Abstract National service systems in child healthcare are characterized by diversity and complexity. Primary, secondary, tertiary and quaternary healthcare services create complex networks covering pediatric subspecialties, psychology, sociology, economics and politics. Can pediatrics exist without philosophy? Does the absence of integrating philosophical perspectives during conceptualization of pediatric care contribute to deficiencies in the service systems structuring child healthcare? Philosophy offers new ways of complex systems thinking in scientific and clinical pediatrics. Philosophy could improve coping strategies on different levels when dealing with ethics of research projects, individual child healthcare and crises of healthcare service systems. Boundary and ultimate situations experienced by severely sick children require help, hope and resilience. Patients and families as well as pediatricians and other caregivers must act in concert. All of them may benefit from consulting with philosophers. The aim of this article is to point out the risks of a strict separation of scientific insight and sensory experience affecting child healthcare in our modern society, which is dominated by technology, competition and lack of equity and time.